Pulse oximeter measurement error of oxygen saturation in patients with SARS-CoV-2 infection stratified by smoking status. Issue 5 (17th November 2022) - Crooks, Colin J.; West, Joe; Morling, Joanne R.; Simmonds, Mark; Juurlink, Irene; Briggs, Steve; Cruickshank, Simon; Hammond-Pears, Susan; Shaw, Dominick; Card, Timothy R.; Fogarty, Andrew W.
As pulse oximeters are now so widely used, it is important to identify any patient groups in whom they may also have a systematic bias that may impair the delivery of medical care to these individuals. One group would be tobacco smokers [1–3], as the inhaled carbon monoxide modifies the haemoglobin molecule within 1–2 min of inhaling tobacco smoke [4], and the subsequent increase in blood carboxyhaemoglobin levels modifies the pulse oximetry signal [5]. This was reported in a series of 16 patients with carbon monoxide poisoning from 1994 which resulted in higher pulse oximetry measurements than the true values, with the comment that this phenomenon may also extend to oxygen saturation measured in smokers as well [6]. To date, no robust real-world clinical data on acutely unwell patients exist to clarify the impact of smoking status and blood carboxyhaemoglobin levels on the measurement error of oxygen saturation by pulse oximeters. There is substantial measurement error in pulse oximetry readings of oxygen saturation below 90% which is not due to smoking status https://bit.ly/3RunKtL